The Effect of Conceptual Understanding Procedures Learning Model on Students' Higher Level Thinking Skills - Wahyu Nurhidayat; Endang Surahman; Eko Sujarwanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Learning activities tend to be teacher-centered with conventional learning methods. In addition, the indicators trained are limited to C4 (analyzing) indicators. This has an impact on students' higher order thinking skills. This study aims to analyze the effect of the conceptual understanding procedures learning model on students' higher order thinking skills. This study uses a quasi-experimental research method with a quantitative research approach. The type of research design used is a non-equivalent control group design. The subjects in this study were students science class in senior high school with a study population of 205 students. The sampling technique used is cluster random sampling. The data collection technique used was a description test of 7 questions then measured using the t test. The results showed that the Conceptual Comprehension Procedure learning model had a significant effect on students' higher order thinking skills. This research has implications for the student learning process so that it can become an evaluation lesson for teachers to improve the quality of learning, especially with regard to training students' higher order thinking skills.